Fish from the Ōtata midden: change and continuity in pre-European Māori fisheries - Campbell, Matthew; Walter, Richard; Sabetian, Armagan; Furey, Louise; Ash, Emma; McAlister, Andrew; Zhang, Jingjing; Haylock, Caitlin (Frontiers in Environmental Archaeology, 2025)
The stratified midden on Ōtata Island, in New Zealand's Hauraki Gulf, dates from the fourteenth century CE, soon after the East Polynesian settlement of New Zealand, to the eighteenth century, just prior to the arrival of Europeans. Analysis of the fishbone assemblages shows that the main targeted species throughout the sequence was snapper (Chrysophrys auratus), accounting for between 50 and 88% of each assemblage. Cranial bones of snapper significantly outnumbered vertebrae, demonstrating that snapper bodies were being preserved for off-site consumption. This pattern is not apparent for other fish species. An early focus on individual fish capture, with benthic or reef species more common than in later assemblages, was superseded by an emphasis on pelagic schooling species, indicating increased use of netting both in response to demographic pressures and as netting technology developed. Snapper size reconstructions for Occupation 3 were significantly skewed toward smaller fish as the environment recovered from the eruption of the nearby Rangitoto volcano and deposition of tephra on the seabed. Otolith trace element analysis showed that juvenile snapper behaviors remained consistent throughout the sequence, but that there were subtle environmental changes. These are attributed to anthropogenic terrestrial changes, but otherwise there were no measurable anthropogenic changes to marine ecosystems.